ASPEK HUKUM PENGATURAN RUANG UDARA DI ATAS IBUKOTA NEGARA NUSANTARA UNTUK KEPENTINGAN PERTAHANAN DAN KEAMANAN NEGARA - Novi Sujatmiko; Bambang Widarto; Agus Suprapto (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
The Capital City is the center of government and serves as a representative symbol of the Indonesian nation. It is one of the vital national objects that must be protected from various potential threats, both domestic and foreign. The most immediate and potentially damaging threat is one that comes from the air, such as aircraft, helicopters, drones, and other aerial vehicles. Airspace security over the Capital City is carried out by countries by deploying national defense forces with the aim of preventing sudden attacks. In addition to defense equipment capable of repelling or stopping such threats, appropriate legal regulations are needed to accommodate the deployment of defense forces in the Capital City. This study aims to analyze the legal framework governing airspace defense over the Capital City and evaluate its adequacy in addressing modern aerial threats. The research uses a normative legal method with a statutory and conceptual approach, focusing on national laws, international aviation and defense regulations, and comparative practices from other countries. The results show that current Indonesian regulations acknowledge the importance of securing airspace over vital national objects but lack specific, integrated legal instruments for swift military response. Coordination between civil aviation and defense institutions remains unclear. Although the 1944 Chicago Convention does not regulate the airspace over presidential complexes in detail, it provides for prohibited and restricted areas under Article 9(a) for national defense. In practice, countries designate prohibited areas over state palaces and central government offices, with surrounding restricted areas to balance civil aviation and security interests.